2014
DOI: 10.1055/s-0034-1385922
|View full text |Cite
|
Sign up to set email alerts
|

Low “quotient” Lp(a) Concentration Mediates Autoimmune Activation and Independently Predicts Cardiometabolic Risk

Abstract: Elevated plasma lipoprotein [Lp](a) is a recognized cardiovascular risk factor [1][2][3]. It uses atherogenic and prothrombotic pathways via systemic inflammation and endothelial dysfunction. Its glycoprotein apo(a), bound to apoB moiety, is very heterogeneous in size due to a genetically determined kringle IV type 2 copy number variation within the LPA gene on chromosome 6q27 [4]. Risk of coronary heart disease (CHD) is considered to be determined by Lp(a) level which is mediated by LPA variants. Kringle IV t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
21
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 29 publications
5
21
0
Order By: Relevance
“…By adjusting the Lp(a) concentration for the effects of the LPA rs10455872 A>G polymorphism, age, gender, total cholesterol, and fasting insulin, we estimated the expected Lp(a) concentration in each of the 1669 participants to determine the quotient between observed and expected Lp(a) values. Cox regression models (also comprising smoking status, systolic pressure, and serum HDL-cholesterol) disclosed that, compared with the mid-tertile, both low and high Lp(a) quotient tertiles significantly predicted incident CHD, especially in women, after 5.1 years of follow-up 20. This was consistent with the notion that ‘low’ serum Lp(a) reflects autoimmune activation 9.…”
Section: Introductionsupporting
confidence: 78%
“…By adjusting the Lp(a) concentration for the effects of the LPA rs10455872 A>G polymorphism, age, gender, total cholesterol, and fasting insulin, we estimated the expected Lp(a) concentration in each of the 1669 participants to determine the quotient between observed and expected Lp(a) values. Cox regression models (also comprising smoking status, systolic pressure, and serum HDL-cholesterol) disclosed that, compared with the mid-tertile, both low and high Lp(a) quotient tertiles significantly predicted incident CHD, especially in women, after 5.1 years of follow-up 20. This was consistent with the notion that ‘low’ serum Lp(a) reflects autoimmune activation 9.…”
Section: Introductionsupporting
confidence: 78%
“…If oxidation of Lp(a) is also reduced by bilirubin, the apparent Lp(a) concentration will not be decreased subsequently. Onat A et al reported that Lp(a) was positively associated with total cholesterol, and negatively associated with fasting insulin [26]. The directions of the correlation of Lp(a) with these variables seem to be in concordance with those of baseline bilirubin.…”
Section: Discussionmentioning
confidence: 78%
“…We speculate that these findings may support the idea that changes in lipoprotein[Lp](a) might be related to the underlying mechanism. Lp(a) mediates systemic inflammatory process and endothelial dysfunction, and acts as one of the cardiovascular risk factors, and it utilizes atherogenic and prothrombotic pathways [26,27]. Bilirubin exerts antioxidant activity on low-density lipoprotein [17,28,29].…”
Section: Discussionmentioning
confidence: 99%
“…Of interest is our finding that higher baseline LDL-cholesterol levels are associated with a reduced risk for 4-year incident diabetes as other diabetes risk models have not identified LDL-cholesterol as an independent predictor of diabetes [3,6,16]. Associations between LDL-cholesterol subfractions, e.g., lipoprotein (a), and risk for diabetes have been inconsistent [17,18]. However, lipid lowering with statin medications has been associated with increased diabetes risk in both epidemiological studies [19][20][21][22] and meta-analyses of prospective clinical trials [23][24][25].…”
Section: Discussionmentioning
confidence: 99%